The 22-Item Sinonasal Outcome Test as a Tool for the Assessment of Quality of Life and Symptom Control in Allergic Rhinitis. Issue 2 (March 2020) - Husain, Qasim; Hoehle, Lloyd; Phillips, Katie; Caradonna, David S.; Gray, Stacey T.; Sedaghat, Ahmad R.
Background: The 22-item Sinonasal Outcome Test (SNOT-22) is a validated patient-reported outcome measure for chronic rhinosinusitis and in many circumstances is used in rhinology/otolaryngology clinics to assess sinonasal symptoms in general when a formal diagnosis is not established, although with little support for such usage. Objective: To assess the utility of the SNOT-22 as a reflection of quality of life (QOL) and symptom control for patients with allergic rhinitis (AR). Methods: Retrospective review of 353 patients with persistent AR. Each patient completed a SNOT-22, 5-item EuroQol general health-related QOL (EQ-5D) questionnaire (from which the visual analog scale [VAS] was used), and Rhinitis Control Assessment Test (RCAT). In addition, 95 patients also completed these questionnaires 1 to 12 months later. Results: The SNOT-22 was negatively correlated with the EuroQol 5-dimensional visual analog scale (EQ-5D VAS; r = −.45, 95% confidence interval [CI]: −0.53 to −0.36, P < .001) and RCAT ( r = −.62, 95% CI: −0.68 to −0.55, P < .001), with excellent internal consistency. The SNOT-22 demonstrated responsiveness, with mean change of −5.8 (95% CI: −8.9 to −2.6, P < .001) from pre- to posttreatment. The change in SNOT-22 over the treatment period was correlated with change in EQ-5D VAS ( r = −.28, 95% CI: −0.46 to −0.07, P = .008) and RCAT ( r = −.56, 95% CI: −0.69 to −0.41, P < .001). The minimal clinically important difference was calculated to be between 6 and 11. Conclusion: The SNOT-22 has utility to assess QOL and symptom control in AR, and it is both reliable and responsive in its application to patients with AR. The SNOT-22 may therefore be a convenient and versatile tool in the clinical assessment of patients with AR.